Eye Moving Desensitization And Reprocessing Untuk Mereduksi Trauma Pada Korban Kekerasan Dalam Rumah Tangga - Hengki Satrianta (Pusat Studi Wanita, Univesitas Kristen Indonesia, 2022)
Domestic violence cases shown increased from time to time. Victims of domestic violence are dominated by women and are vulnerable to trauma. Efforts are being needed to deal with trauma so that it does not cause a more negative impact. One of the efforts that can be done is through Eye Moving Desensitization and Reprocessing (EMDR). This study aims to determine whether EMDR is able to reduce trauma to victims of domestic violence. This research is a quantitative research with experimental type. The design used is the one group pretest-posttest design. The sample in this study estimeated purposively with a total of three peoples. Data were collected using a scale technique. Data were analyzed using sign test. The results showed that EMDR was able to reduce the level of trauma in victims of domestic violence